2021
DOI: 10.1186/s12872-021-01853-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality and adverse events in patients with infective endocarditis: a retrospective real world study in a surgical centre

Abstract: Purpose Mortality in infective endocarditis (IE) is still high, and the long term prognosis remains uncertain. This study aimed to identify predictors of long-term mortality for any cause, adverse event rate, relapse rate, valvular and ventricular dysfunction at follow-up, in a real-world surgical centre. Methods We retrospectively analyzed 363 consecutive episodes of IE (123 women, 34%) admitted to our department with a definite diagnosis of non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
4
18
0
Order By: Relevance
“…This suggests improvement in rates of surgical procedures especially for patients with complicated IE. Intravenous drug use was strongly associated with complicated IE, and it was an independent predictor of mortality and new episodes of endocarditis, as has been reported previously [13,24].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This suggests improvement in rates of surgical procedures especially for patients with complicated IE. Intravenous drug use was strongly associated with complicated IE, and it was an independent predictor of mortality and new episodes of endocarditis, as has been reported previously [13,24].…”
Section: Discussionsupporting
confidence: 80%
“…One important reason for this could be that such patients seek medical care sooner and hence get earlier treatment, which has been shown to improve complications and mortality [26]. However, previous studies have reported a higher association of mortality with prosthetic valve endocarditis and double valve infection [6,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as previously reported [ 10 ], drug abusers had a more than doubled long-term risk of death at multivariate analysis (HR 2.3, 95%CI 1.1–4.7, p = 0.015), adjusting for age (HR per unit 1.034, 95%CI 1.018–1.050, p < 0.001), EuroSCORE II (HR per unit 1.015, 95%CI 1.008–1.023, p < 0.001), double-valve infection (HR 2.0, 95%CI 1.4–3.0, p < 0.001), and Streptococcus infection (HR 0.5, 95%CI 0.3–0.8, p = 0.009), which were the variable retained in the final model.…”
Section: Resultssupporting
confidence: 57%
“…Age and gender distribution in our collective was similar to those of other large spondylodiscitis [ 10 ] and endocarditis [ 6 ] collectives. Patients with IE showed typical distributions of affected valves [ 26 ]. Localization of spondylodiscitis did not differ between the S and SIE groups and coincide with literature findings [ 19 ].…”
Section: Discussionmentioning
confidence: 99%